The use of assistive technology for symbol identification by children with Rett syndrome. - Hetzroni O; Rubin C; Konkol O (Journal of Intellectual & Developmental Disability, 2002)
This study was designed to investigate whether the use of assistive technology would assist in the ability to identify symbols by girls with Rett syndrome. Rett syndrome is a neurological disorder manifested mainly in girls who lose most of their communication abilities between 6 and 18 months. Six types of meaningful referents (true name, storybook, song, food, verb and communication) were selected from their individualised educational programme. An individualised multimedia programme was created in order to facilitate the ability to match spoken words to symbols. A multiple probe design across four symbol sets was used to assess the identification of graphic and orthographic symbols with three girls who were in the third clinical stage of Rett syndrome. The results demonstrate a steady learning curve across symbol sets and a partial retention of knowledge throughout maintenance probes. Implications and future research directions are discussed.